2019
DOI: 10.1177/0022034519837248
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Signatures in Mandibular Ameloblastoma Correlate with Smoking

Abstract: Ameloblastoma is a rare tumor of odontogenic epithelium, the low incidence rate of which precludes statistical determination of its molecular characterizations. Despite recent genomic and transcriptomic profiling, the etiology of ameloblastomas remains poorly understood. Risk factors of ameloblastoma development are also largely unknown. Whole exome sequencing was performed on 11 mandibular ameloblastoma samples. We identified 2 convergent mutational signatures in ameloblastoma: 1) a signature found in multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 38 publications
(47 reference statements)
2
32
0
Order By: Relevance
“…In the present study only 18% patients were smokers and 82% were non smokers. This study agrees with that of Guan et al 2019 25…”
Section: Discussionsupporting
confidence: 94%
“…In the present study only 18% patients were smokers and 82% were non smokers. This study agrees with that of Guan et al 2019 25…”
Section: Discussionsupporting
confidence: 94%
“…Recently, Guan et al . ( 6 ) reported a Whole-Exome Sequencing (WES) study on Ameloblastoma and confirmed the influence of tobacco on the somatic mutation, supporting its role in the tumorigenesis.…”
Section: Introductionmentioning
confidence: 92%
“…Due to the invasive potential and high recurrent rate, the surgical resection often has a margin of at least 1 cm from the margin of the tumor, leading to profound facial defects and morbidity ( 2 ). Conservative options like enucleation or curettage often result in a high recurrence rate ( 5 , 6 ). The alternative management of radiation therapy has a limited application in Ameloblastoma because of the risk of malignant transformation ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ameloblastoma (AB), a common odontogenic epithelial neoplasm, exhibits locally invasive and aggressive behaviors ( 1 ). More than 80% of AB cases occur in the mandible ( 2 ). It has up to 90% risk of recurrence following conservative treatment ( 3 ).…”
Section: Introductionmentioning
confidence: 99%